Avanços e impasses na garantia dos direitos humanos das pessoas com transtornos mentais autoras de delito - Correia, Ludmila Cerqueira (2007)
The present work analyses the advances and setbacks in the assurance of human rights of those who are criminally insane, hospitalised in Custody and Psychiatric Treatment Hospitals (CPTH). Theoretical revision was held on the constitution of the asylum institution, emphasising the concept of social dangerouness, which still supports the segregationalist asylum assistance model. Discussions are held about topics on the Brazilian penal system related to the criminally insane, emphasising the creation and consolidation of precautionary action, besides approaching the matter of healthcare at CPTH and the reaffirmation of this segregationalist, excluding model. The contemporaneous concept of human rights was taken as a reference, taking into consideration the condition of subjects of rights of this vulnerable group. There is still a bibliographical revision on the field of Human Rights and Mental Health, having as a parameter the international and national instruments of protection to the human rights, emphasising those specific of the handicapped or mentally insane. Emphasis is given to the Psychiatric Reform Movement, which has supported proposals of reorientation of the hegemonic assistance model in Mental Health, and the national policies on it. The possibilities of changes in the model of attention and Mental Health of those criminally insane in Brazil, following the principal of the psychiatrist reform and the Law nº 10.216/2001. The analysis of the implementation of the assurance of human rights for the criminally insane was analized through a case study at Custody and Treatment Hospital of Bahia. There was data collection related to HCT-BA and the analysis of data orientated by the principles of qualitative research. It was verified that, although some changes had been made at the hospital, the institution has preserved its asylum characteristics, making clear a tradition based on the negation of human rights of those hospitalized. Finally, experiments previously started in Brazil are presented, aiming to reorient the model of attention to the criminally insane. The improvement of the legislation, per se, does not guarantee the materialization of recent strides gained through the Psychiatric Reform, particularly in relation to criminals with mental disorders.